KISS Berbanding Multilevel Approach - Muhammad Ali Napiah Lubis; Samrul Bahri Hutabarat (Universitas Batanghari Jambi, 2023)
Management is very urgent and needed in managing institutions, businesses and organizations, because without measurable management the journey of institutions, businesses and organizations will find many difficulties in achieving goals. In maximizing work as a team to achieve organizational goals, four actions are introduced in management science, namely coordination, integration, simplification and synchronization, which is abbreviated as